2018
DOI: 10.3389/fpsyg.2017.02318
|View full text |Cite
|
Sign up to set email alerts
|

How Person-Organization Fit Impacts Employees' Perceptions of Justice and Well-Being

Abstract: Regulatory fit theory predicts that when individuals adopt strategies that sustain their motivational orientations, they feel right about what is happening. Our aim was to test these predictions at the person-organization level. Across three studies, we expected and found that a feeling right experience that results from a match between an employee and an organizational climate produces perceptions that the company's prevailing procedures are fair. In Study 1 (N = 300), a survey among employees of distinct com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…This is an important factor in predicting individuals’ attitudes and behaviors ( Kristof, 1996 ). When the individual’s values, capacity, and demand and the organizational values, job requirements (specification), as well as remuneration system fit well, individuals will experience higher job satisfaction ( Jin et al, 2018 ; Roczniewska et al, 2018 ), organizational commitment ( Bahat, 2020 ), lower work-related pressure ( Gould-Williams et al, 2015 ), and lower turnover intention ( Memon et al, 2018 ). At the same time, they will also implement more pro-organizational behaviors, such as performance behaviors ( Goodman and Svyantek, 1999 ), organizational citizenship behaviors ( Kristof-Brown et al, 2005 ; Hoffman and Woehr, 2006 ), and innovative behaviors ( Afsar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important factor in predicting individuals’ attitudes and behaviors ( Kristof, 1996 ). When the individual’s values, capacity, and demand and the organizational values, job requirements (specification), as well as remuneration system fit well, individuals will experience higher job satisfaction ( Jin et al, 2018 ; Roczniewska et al, 2018 ), organizational commitment ( Bahat, 2020 ), lower work-related pressure ( Gould-Williams et al, 2015 ), and lower turnover intention ( Memon et al, 2018 ). At the same time, they will also implement more pro-organizational behaviors, such as performance behaviors ( Goodman and Svyantek, 1999 ), organizational citizenship behaviors ( Kristof-Brown et al, 2005 ; Hoffman and Woehr, 2006 ), and innovative behaviors ( Afsar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, this work by Camacho et al (2003) and Roczniewska et al (2018) reveals that when the decision-making process "feels right," the decision itself (i.e., the outcome) is experienced as "being right." Furthermore, although regulatory fit makes all kinds of activities feel right, this experience of rightness itself creates a special, second-order fit with decision-making activities in particular because these activities are fundamentally about truth-seeking.…”
Section: Making a Decision In A Manner That "Feelsmentioning
confidence: 95%
“…More recent research has identified parallel effects of regulatory fit at levels beyond the individual. For example, evaluations of procedural justice are similarly affected by regulatory fit at the person‐organizational level (Roczniewska et al., 2018). Across three studies, Roczniewska and colleagues (2018) examined regulatory fit between individual employees’ regulatory focus (promotion versus prevention) and the regulatory focus of their organization.…”
Section: Making a Decision In A Manner That “Feels Right”mentioning
confidence: 99%
“…This seems important because the perspective of the group whose status quo is maintained may be neglected in messaging about the change because their objective circumstances have not changed. Their psychological perceptions, however, including their experience of unfairness, could be negatively affected ( Roczniewska et al, 2018 ). Thus, it is important to consider what could be done about this.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, processing fluency may contribute to the “feeling right” phenomenon when individuals are exposed to persuasive messages that match their orientation. Interestingly, research has demonstrated that regulatory fit increases fairness perceptions ( Li et al, 2011 ; Roczniewska et al, 2018 ). When individuals read decision justifications that match their focus, they deem the situation more just (Roczniewska and Higgins, unpublished).…”
Section: Introductionmentioning
confidence: 99%